Tuberculosis meningitis coexisting with HIV Infection: a comprehensive review - Navasardyan, Inesa; Abdou, Alexander; Kades, Samuel; Misakyan, Yura; Ochsner, Jacob; Subbian, Selvakumar; Venketaraman, Vishwanath (Frontiers in Tuberculosis, 2023)
Mycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis (TB) in humans, Although Mtb is primarily considered as a respiratory pathogen, its ability to spread to and affect the central nervous system (CNS) is of particular interest due to its clinical importance. Tuberculosis meningitis (TBM) is described as the manifestation of Mtb infection in the meninges, leading to inflammation and disease. Individuals with a weakened immune system, particularly those infected with human immunodeficiency virus (HIV), are more susceptible to both pulmonary and extra-pulmonary Mtb infection. HIV infection leads to a gradual depletion of CD4 T-cells, severely impairing the host immune response against pathogens and, thus, predisposes one to several opportunistic infections, including Mtb. Herein, we discuss the current knowledge, potential therapeutic agents, mechanisms of action, and describe various in vivo and in vitro models that may be used to study TBM co-existing with HIV infection.